Fortificações na Amazônia - Graciete Guerra da Costa (Navigator)
This communication is part of a project about Fortifications in Amazon from 1616 to 1750. It analyzes the political context, the geopolitics, and the sociology of the Conquest. This work studies the Fortifications in the Brazilian Amazon and the particular characteristics of military architecture typical of the region in the middle of the 17th and 18th centuries. The Portuguese Crown politics of fortifying, demarcating, occupying and populating their territories is part of a pombalina decision to substitute religious missions for freguesias, in the domain of the military, to representatives of the king and some members of the secular clergy. Territorial divisions laid by properties of the Church were legitimized by the civil society. The founding of forts and cities in the Amazonas river valley replaced religious missions. Nominations of those villages with portuguese names like Almeirim, Santarém, Óbidos and others, and the making of an urbanistic plan according to portuguese cities gave a portuguese look to the valley’s population. This paper argues that those changes reflect a new territorial division in that period of transformations in the toponymy.